Pachytene Analysis in a Human Reciprocal (10;11) Translocation - Ferguson-Smith, M. A. (1973)
Pachytene quadrivalents are described in a male heterozygous for a balanced reciprocal translocation between the long arms of chromosomes 10 and 11. The break points of the translocation occur at 10q23 and 11q24. The main chromomere patterns of the bivalents correspond to the main G bands in mitosis and are sufficiently pronounced to allow the identification of bivalents 10 and 11 in normal spermatocytes.